Comparative Analysis of Root Traits and the Associated QTLs for Maize Seedlings Grown in Paper Roll, Hydroponics and Vermiculite Culture System - Liu, Zhigang; Gao, Kun; Shan, Shengchen; Gu, Riling; Wang, Zhangkui; Craft, Eric J.; Mi, Guohua; Yuan, Lixing; Chen, Fanjun (Frontiers in Plant Science, 2017)
Root system architecture (RSA) has an important role in nitrogen (N) and phosphorus (N) acquisition, but RSA is seldom considered as a selection criterion to improve nutrient uptake efficiency in crop breeding as roots are greatly influenced by uncontrolled environment factors under field conditions. Therefore, it is necessary to develop fast selection methods for evaluating root traits of young seedlings in the lab which can then be related to high nutrient efficiency of adult plants in the field. Here, a maize recombination inbred lines (RILs) population was used to compare the genetic relationship between RSA and nitrogen and phosphorous efficiency traits. The phenotypes of eight RSA-related traits were evaluated in young seedlings in three different growth systems (i.e. paper roll, hydroponics and vermiculite), and then subjected to correlation analysis with N efficiency and P efficiency related traits measured under field conditions. Quantitative trait loci (QTL) of RSA were determined and QTL co-localizations across different growth systems were further analyzed. Phenotypic associations were observed for most of RSA traits among all three culture systems. Correlations of RSA-related traits in hydroponics and vermiculite with N (NupE) uptake efficiency (r = 0.17-0.31) and P (PupE) uptake efficiency (r = 0.22-0.34) were significant but weak, and not in paper roll. A total of 14 QTLs for RSA were identified in paper rolls, 18 in hydroponics, and 14 in vermiculite. Co-localization of QTLs for RSA traits were identified in six chromosome regions of bin 1.04/1.05, 1.06, 2.04/2.05, 3.04, 4.05 and 5.04/5.05. These results suggest the difficulty that uses the phenotypes from one growth system to predict those in another growth system. Additionally, RSA traits at seedling stage with hydroponics and vermiculite systems is better than paper roll system to be used as an important index to accelerate the selection of high N and P efficiency genotypes for maize breeding programs.